THE STRANGE AND FAMILIAR ETERNITY. THE EXPERIENCE OF GOD IN CONTEMPORARY HUNGARIAN LYRICAL WORKS - SZILVESZTER, László Szilárd (Studia Universitatis Babeș-Bolyai Philologia, 2020)
The Strange and Familiar Eternity. The Experience of God in Contemporary Hungarian Lyrical Works. While in the second part of the 20th century Hungarian literary criticism, the topic of sacrality in lyrical poetry was quite emphatically present in many scientific studies (e.g. in György Rónay’s, László Rónay’s, György Rába’s, and Éva Cs. Gyimesi’s works), this area has been unfairly neglected for the past few decades. We might say that, apart from a few lucky exceptions, among the contemporary lyrical analyses, one can hardly find a study that focuses mainly on the various motifs of Christianity, the aesthetic-poetic characteristics of transcendental experience, and the forms of expression of faith and doubt. The essay examines transcendental experiences in contemporary Hungarian poetry, and seeks to identify that attitude of the modern author, which can be described as a dialog-based approach to the Christian tradition. In this paper, we propose to present those aesthetic-poetic initiatives in István Bella’s, István Ágh’s, and Imre Oravecz’s lyrical works, in which the relations between man and sacrality are reevaluated, as well as the role of poetry and the entire modern culture. REZUMAT. Eternitatea familiară și străină. Experiența sacralității în poezia maghiară contemporană. În timp ce în a doua parte a secolului 20 aspectul sacralității, relațiile dintre om și Dumnezeu au fost reprezentate destul de intens în analiza și critica literară maghiară (de ex. György Rónay, László Rónay, György Rába, Éva Cs. Gyimesi), în ultimele două decenii, aceste subiecte au fost în mod nedrept ignorate. Am putea afirma că – în afară de câteva excepții – cercetările literare contemporane au neglijat studierea experienței transcendentale, apariția valorilor creștinismului, caracteristicile estetico-poetice ale credinței și îndoielii, deși în lirica contemporană aceste valori sunt prezente cel puțin în aceeași măsură ca și în creațiile literare de dinaintea celui de-al Doilea Război Mondial. Studiul propune o analiză asupra prezenței sacralității în poezia maghiară contemporană, bazându-se pe o scurtă prezentare a liricii lui István Bella, István Ágh, Imre Oravecz. Cuvinte-cheie: lirica maghiară, literatura contemporană, transcendență, credință și dubiu, creștinism